POTENTIAL CONTRIBUTING FACTORS FOR MULTI-ETHNIC INTEGRATION IN A MULTINATIONAL ORGANISATION IN SOUTH AFRICA - Naidoo, Yogashan Spiro (My University, 2012)
The purpose of this research was to identify the potential contributing factors for multi-ethnic integration in a multinational corporation in South Africa. The case site was ArcelorMittal South Africa’s Vanderbijlpark business unit. The objective of the case study was two-fold: · Identify what the business unit has done thus far with respect to creating an inclusive environment for its entire multi-ethnic workforce. · Identify gaps in the system with associated recommendations to improve the situation. Seven research propositions were developed from the literature review. The research methodology adopted to test these propositions was qualitative analysis. Data was collected via one-on-one interviews and these were conducted at a case site i.e. ArcelorMittal South Africa’s Vanderbijlpark business unit. The data analysis spiral model as proposed by (Creswell 1998) was used to analyse the data. The research findings concluded that: · A leader’s business experience will contribute towards multi-ethnic integration within multinational organisations in South Africa. · A leader’s level of international exposure will contribute towards multi-ethnic integration within multinational organisations in South Africa. · An organisation’s level of internationalisation will contribute towards multiethnic integration within multinational organisations in South Africa. · An organisation’s recruitment practices that actively seek ethnic heterogeneity will contribute towards multi-ethnic integration within multinational organisations in South Africa. ii · Practicing educational awareness aimed at recognising workforce differences and benefits will contribute towards multi-ethnic integration within multinational organisations in South Africa. · Practicing fair promotion and reward of employees from different ethnicities will contribute towards multi-ethnic integration within that organisation in South Africa. · There is however partial agreement that an organisation’s internal structures will contribute towards multi-ethnic integration within that organisation. The key recommendations include: Vanderbijlpark’s site management needs to make a conscious effort of educating their employees with respect to the different ethnic groups working at the business unit. As part of a continuous awareness program, the unit’s business communication needs to sensitise the employees of the different ethnic groups present, their important religious ceremonies, holidays and value/belief system pertinent to those different ethnic groups. An inclusive environment conducive to multi-ethnic integration needs to be cultured into the organisation. The business unit needs to develop and implement a policy that dictates disciplinary action, including the possibility of dismissal, will be enacted upon those individuals who contravene the shared values of the organisation. Vanderbijlpark’s management needs to remind its staff that English is to be the spoken language in any meeting that includes individuals from different ethnic groups, irrespective of whether they are literate in the language. The Human Resources team at the Vanderbijlpark site need to investigate and apply a more effective evaluation system when it comes to testing candidates applying for management positions. The metrics need to place an emphasis on the individual’s leadership skills especially their ability to work in multi-ethnic environments. iii As part of their training program, potential leaders of the organisation need to be introduced to the subject of “glocalisation” and how it is to be applied in organisational settings. The Vanderbijlpark site needs to review its selection criteria with respect to who should attend educational awareness training programs e.g. programs regarding ethnic diversity awareness. Management representation is imperative at programs that address leadership issues. At the same time thought needs to be applied when the groups are selected. There has to be a balance in the group between cynics and optimists. “If you believe it you will see it”
MBA thesis - WBS
Keywords: Multi-ethnic integration; Multinational companies